2020
DOI: 10.1177/0091415020944405
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Depression and Their Predictors in a Population-Based Study of Korean Older Adults

Abstract: The aim of this study was to determine trajectories of depression in older adults and to identify predictors of membership in the different trajectory groups. A total of 3983 individuals aged 65 or older were included. Latent class growth models were used to identify trajectory groups. Of 3983 individuals, 2269 (57%) were females, with a mean baseline age of 72.4 years ( SD = 6 years). Four depression trajectories were identified across 8 years of follow-up: “low-flat” ( n = 3636; 86.6%), “low-to-middle” ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…This is also supported by previous studies (27,28). Most chronic diseases have a long course and may even require lifelong treatment, affecting their quality of life and increasing the financial burden on families, which may trigger and exacerbate the onset and progression of depression (29). Furthermore, this study found that sleep duration 6-8 h and >8 h were protective factors against depressive symptoms in older adults in both urban and rural areas, relative to sleep duration <6 h. It has been confirmed that adjusting sleep duration decreases the incidence of depressive symptoms (30).…”
Section: Discussion Risk Factors a Ecting Depressive Symptoms In Th...supporting
confidence: 80%
“…This is also supported by previous studies (27,28). Most chronic diseases have a long course and may even require lifelong treatment, affecting their quality of life and increasing the financial burden on families, which may trigger and exacerbate the onset and progression of depression (29). Furthermore, this study found that sleep duration 6-8 h and >8 h were protective factors against depressive symptoms in older adults in both urban and rural areas, relative to sleep duration <6 h. It has been confirmed that adjusting sleep duration decreases the incidence of depressive symptoms (30).…”
Section: Discussion Risk Factors a Ecting Depressive Symptoms In Th...supporting
confidence: 80%
“…The KHPS is an official database carried out by the Korea Institute for Health and Social Affairs and the National Health Insurance Service since 2008. More detailed descriptions of the study design and profile have been published elsewhere 16 . Briefly, the purpose of KHPS is “to generate basic data on individual healthcare behaviors, health level, usage of health services, and healthcare expenditures”.…”
Section: Methodsmentioning
confidence: 99%
“…More detailed descriptions of the study design and profile have been published elsewhere [ 48 ] . Briefly, KHPS used a stratified sampling frame taken from the Korean Population and Housing Census in 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates included sex, age, education, marital status, residential area, number of members in the household, household composition type, housing type, current chronic disease status, private health insurance, household income quantile, and household expense [ 48 ]. Age was categorized as 65–69, 70–74, 75–79, and 80 years and older.…”
Section: Methodsmentioning
confidence: 99%